Women in IT Management: Significant Gains and Continuing Challenges. Issue 3 (3rd May 2020) - Johnson, Vess L.; Kiser, Angelina; Kappelman, Leon
ABSTRACT: The roles of women in the workforce have changed significantly over the past several decades. While there has been considerable progress made by women into leadership positions, this progress has been slow. This article explores factors that may impact the ability of women in information technology (IT) to move into leadership positions. Data collected for the Society of Information Management IT Trend Study for 2015, 2016, and 2017 were analyzed, and corporate characteristics that impact female advancement into leadership positions were explored. Results suggest that there are opportunities for women in IT. The percentage of women in positions of leadership is steadily increasing in a wide range of industries. However, there is an evidence to suggest that industry's gender composition as well as company size (revenue) may impact the gender of the IT leader. Also, some interesting differences in performance measures based on the leader's gender are discussed.